Pengaruh Packaging Produk Terhadap Peningkatan Penjualan Produk - Maharani, Bintang; Pratama, Egi Nanda; Hulu, Leli Nofentri; Alfarezi, Muhammad Hadits (ISTIKHLAF: Jurnal Ekonomi, Perbankan dan Manajemen Syariah, 2024)
In addition to its protective function, packaging is an important marketing tool that can influence consumer perceptions and purchasing behavior. Aesthetically pleasing and useful packaging is essential to attract customers in a very tight industry. The purpose of this study is to investigate how product packaging affects the increase in product sales in packaging aspects such as materials, design, and information conveyed. Literature study is the methodology used, where researchers collect and examine information about product packaging and its impact on sales from various reliable sources. This research shows how well-designed packaging can increase visual appeal and provide clear information to customers, which can influence their decision to purchase. In addition, customers who are concerned about the environment are starting to give additional weight to eco-friendly packaging. Based on the results of this study, it can be said that good product packaging serves as a marketing tactic that can increase sales and competitiveness in addition to protecting goods. It is hoped that this research can provide valuable information for companies to create more effective packaging methods that can maximize sales